Diagnosis and Prevention of Overheating in Internal Combustion Engines - Pilicita , Josué; Domínguez, Josué; Torresano, Carlos; Salazar, Byron (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Overheating in internal combustion engines, particularly in models such as the 2011 Mazda BT-50, was highlighted as a significant problem due to its impact on engine efficiency and the environment. It was noted that this phenomenon can increase pollutant emissions and deteriorate critical components such as lubricating oil, affecting engine life. According to Briceño and Brayan (2022), the cooling system plays a key role in preventing overheating, as it regulates the temperature through the radiator, water pump and thermostat. Galvez (2020) emphasised the importance of keeping these components in good condition to avoid failures. Diagnosing problems related to overheating involves identifying common causes such as coolant leaks, sediment build-up in the radiator and thermostat or fan malfunctions (Soria, 2023). Solutions include replacement of defective components, cleaning of the cooling system and use of advanced diagnostic tools such as OBD-II scanners. The research highlighted the relevance of preventive maintenance, such as regular inspection and periodic replacement of coolants and thermostats (Patel et al., 2020). Furthermore, the value of new technologies in the automotive industry to develop more efficient and sustainable engines was underlined. Finally, it was concluded that overheating is a multifactorial problem that requires a holistic approach to ensure optimal engine performance and longevity.